A strategic management study of Davao Insular Hotel Company, Inc. - Valdes, Ma. Veronica A. (Animo Repository, 1998)
Davao Insular Hotel, Co. Inc. is the owning company of the multi-awarded hotel in Davao City, the Insular Century Hotel Davao, a first-class international hotel offering 157 rooms. The company belongs to the lodging industry as it satisfies the need for transient/temporary accommodation of travellers/tourists. The threat of entry in the Lodging Industry is low as well as the threat of substitute. However, the intensity of competition is high. The bargaining power of buyers (guests) and the suppliers are also high. The level of profitability in the industry is therefore determined by the level of intensity of competition is high. The bargaining power of buyers (guests) and the suppliers are also high. The level of profitability in this industry is therefore determined by the level of intensity of competition and bargaining power of buyers (guests). The company belongs to a fragmented industry due to the high products differentiation, high labor content and high personal service, low entry barrier, diverse market needs and high inventory or erratic fluctuations. Thus, competing firms in the industry are very dependent on the personalized service offered to the buyers which is a source of competitive advantage. Other sources of advantage are the amenities and facilities enjoyed by the guests catering to their specific needs. These, together with the brand image, standards of high quality service and products, travel transport service availability, proximately to places of business and leisure are the key success factors in the industry. The construction and expansion of hotels and inns, the decreasing occupancy rates, the regional crisis, and the higher accommodation rates versus the neighboring Asian countries pose a big threat to the company. Given the threats in the environment and the decreasing net income of the company, the management is contemplating on its current and future strategic direction. The current strategic state of Davao Insular Hotel is best described by Michael Porters famous stuck in the middle due to lack of clear company strategic direction. To successfully compete and survive in the industry, the company must primarily identify the companys strategic direction what it wants, where it wants to be and how it will be done. Company control must be strengthened through dedicated time and management. Secondly, the company must undertake upgrades in the hotels rooms and amenities to compete with the upcoming hotels. Thirdly, maintain the occupancy rate ate a 60% to expand revenue and improve profitability. Fourth, to increase/maintain the occupancy rate, the company must always provide value for money toward complete customer satisfaction. In this way, the guests would always prefer the hotel since they enjoy high service in a unique resort setting at a good price. Lastly, the company must raise equity to finance the renovation and the continuous improvement in the hotel and its services. In this light, the survival and future success of the company will depend on its ability to analyze the environment and taking an active stance on its strategic direction based on the dynamics of the environment.